Antenna design for Narrowband IoT design, analysis and applications - Pattanaik, Balachandra, 1971- (Advances in computer and electrical engineering (ACEE) book series., 2022)
"The purpose of this book is to provide an antenna design concept for Narrowband Internet of Things Applications and to discuss the variety of antenna design concepts and structures for various industrial requirements"--